A study on the use of New English File Elementary to teach speaking skills to first-year students at the Military Technical Academy - Sầm, Thị Loan (University of Languages and International Studies, 2017)
Vocabulary plays an important role in second language learning process. However, for most of Vietnamese students in general and learners at Hanoi University of Business and Technology (HUBT) in particular, vocabulary seems to be one of the most difficult problems in learning English. As a result, the researcher planned to c onduct an extensive reading program as a mean of vocabulary improvement for first - year students at HUBT. The study was carried out in the form of an action research study on 30 students of class KT 19 - 05. Before the imp lementation , a questionnaire was used to collect information from the students to identify the problem and the causes of the problem. The collected data were analyzed to confirm the assumption that the lack of vocabulary really existed, and the cause of this problem was due to students‟ limit ed reading in class as well as at home. Inspired by positive results in studies about extensive reading, the researcher created a plan of action in which graded readers were used for extensive reading. The action plan was implemented in 10 weeks‟ time. The n, the data were collected from various sources, including questionnaires, a pre - test, a post - test and book reports from students. The findings from the study showed that extensive reading had a positive effect on learners‟ vocabulary acquisition and that there was a significant change in the students‟ attitude towards extensive reading. Based on the findings of the study, some discussion and limitations were presented along with some important pedagogy of implications. Despite the limitations, it is hope d that the study can be used as a reference as well as a source of useful information for other teachers who wish to utilize extensive reading in their class concrete context.